Juridical Analysis of Personal Data Security in the Use of Cloud Computing Technology - Angriawan, Randy; Abadi, Andi Yusril; Jusuf, Ardi M. (Siddiq Institute, 2024)
Cloud computing provides great benefits such as operational efficiency, flexibility, and cost savings. However, this technology also presents serious legal challenges related to personal data protection. This research explores the challenges of implementing personal data protection regulations in Indonesia, such as cross-border jurisdictional issues, unclear responsibilities between users and service providers, and weak compliance monitoring and auditing. In addition, the study found a lack of transparency in data management by cloud service providers, a lack of user education about data security, and the importance of harmonization of regulations at the international level. This study recommends increased collaboration between the government, the private sector, and technology experts, as well as the strengthening of law enforcement mechanisms to ensure optimal protection of personal data in the use of cloud computing.